O-10 Functional and sport performance outcome of players after acl reconstruction sustaining at high-level professional football. (18th November 2016) - Szuba, Lukasz; Czamara, Andrzej; Królikowska, Aleksandra; Krupa, Sebastian; Kentel, Maciej; Reichert, Pawel; Sznajder, Wojciech
Abstract : Background: Return to sport after serious knee surgery which is anterior cruciate ligament reconstruction (ACLR) is very difficult and sometimes unsuccessful process. Main goals of postoperative period is to restore balance, limb symmetry of hamstrings and quadriceps strength and power. Player's recovery to pre-injury level in term of specific sport performance as well as mental awareness of re-injury is a difficult task. From strength and conditioning perspective, landing technique, sudden changes of movement direction are crucial abilities for sport participation and should be sustained on high level after return to play. Objectives: We aimed to assess mid-term functional outcomes after ACLR in professional football players with sport performance outcome – time on the pitch; first team appearances seasons after surgery in comparison to season before injury. Methods: Group I included 17 players who had undergone isolated ACLR using semitendinosus (ST) ipsilateral autograft and successfully return to sport. Postoperatively, they participated in full time professional physical therapy, resulted in return to sport and competition. Group II included 25 players without severe knee ankle injuries. The two groups were matched for age and body mass index (BMI). Functional tests – Figure of 8 Hop Test, Side-Hop and quadriceps/hamstrings torque under isometric conditions measurements were performed at a mean of ±32 months postoperatively (min.23 months). Research of sport participation were conducted to set every player real time's spent on the pitch, based on match protocols, football database's. Results: The limbs with the ACLR had greater LSI = 3% for quadriceps and LSI = 10% for hamstrings isometric torque as compared to uninjured side (p = 0.389, p = 0.077 respectively). The subjects with ACLR had non-significantly higher (p = 0.319) values with regard to dominant side quadriceps and non-significantly lower (p = 0.414) hamstring's peak torque respectively in inter-group comparison. Results of the hop tests showed nonsignificant intra-group side to side differences and significantly faster Side-Hop test performance for Group II in inter-group operated/kicking side comparison (p = 0.028). Return to training in ACL group was ±7, 2 months. Return to match/match time – ±8, 30 months/ ±32, 0 min. Match Time in percentage of pre-injury season - return to sport season 55%, second season after return 92% vs preinjury, at follow-up 104%. Conclusions: At the time of follow-up, the ACLR group had worse functional outcomes in terms of hamstring strength and the results of the Figure of 8 Hop Test, Side-Hop Test. However, bigger inter limb asymmetry was found in non-ACL group with kicking side domination higher than 10% for hamstrings. Soccer player after ACL reconstruction in this cohort had 55% pitch time in return to sport season relatively to preinjury time. Second and at follow-up season time spend on pitch was 92 and 104% respectively as compared to preinjury season. Intergroup comparison revealed that soccer players who had undergone ACLR had less quadriceps and hamstrings strength and worse hop performance.